2021
DOI: 10.1007/s10668-021-01314-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessing drivers of post-harvest losses: tangible and intangible resources’ perspective

Abstract: Many stakeholders in agro-food industry are concerned about sustainability, especially in addressing post-harvest loss (PHL). However, resources available to various supply chain stakeholders such as in the raw cashew nuts (RCNs) supply network to address PHL remain a challenge. The extant literature on PHL has limited intricate insight into its drivers from the perspective of resources. This paper, focusing on RCNs supply network, systematically identifies and analyzes critical drivers that influence PHL guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 135 publications
0
5
0
Order By: Relevance
“…To avoid any bias and validate the framework and the study findings to underpin effective decision-making, a sensitivity analysis was conducted as indicated in existing studies ( Faibil et al., 2021 ; Xia et al, 2015 ). Sensitivity analysis is a process to test the robustness and consistency of a methodology.…”
Section: Study Results and Sensitivity Analysismentioning
confidence: 99%
“…To avoid any bias and validate the framework and the study findings to underpin effective decision-making, a sensitivity analysis was conducted as indicated in existing studies ( Faibil et al., 2021 ; Xia et al, 2015 ). Sensitivity analysis is a process to test the robustness and consistency of a methodology.…”
Section: Study Results and Sensitivity Analysismentioning
confidence: 99%
“…Agricultural grains are prone to rapid deterioration and can be affected by the growth of fungi, yeasts, bacteria, and harmful mycotoxins. Failure to prevent these deterioration processes poses a risk to human consumption, including the consumption of animal products derived from grain-based feeds [86]. One of the key objectives and benefits of post-harvest activities is the loss prevention in the food production system.…”
Section: Post-harvest Main Activitiesmentioning
confidence: 99%
“…Bendinelli et al [17] empirically investigated the representative factors contributing to post-harvest losses of grains (rice, maize, soybean, and wheat) and found that insufficient post-harvest infrastructure, especially in food storage and food marketing, could lead to higher post-harvest losses. Faibil et al [18] found that the main drivers of post-harvest losses in raw cashew nuts were the lack (or insufficient use) of proper packaging materials and insufficient drying technologies and materials. Anand and Barua [19] addressed the key factors of post-harvest wastage of fresh fruits and vegetables under five operational features: demand forecasting, production planning, transportation, inventory, and inefficient harvesting.…”
Section: Literature Reviewmentioning
confidence: 99%